Undergraduate biochemistry student difficulties with topics requiring mathematical skills: use of an online maths skills support site. Issue 2 (15th March 2022) - Watters, Dianne J.; Johnston, Peter R.; Brown, Christopher L.; Loughlin, Wendy A.
ABSTRACT: A number of areas of difficulty in basic numeracy and mathematical skills were identified, which hinder students' success in a foundational biochemistry course. Many students have difficulty with the concepts of pH and buffers (requiring proficiency with logarithms) and enzyme kinetics (requiring algebraic manipulations and graphing). The voluntary use by students of an 'in house' online support site, the Maths Skills Site, to address these difficulties was varied and seemed to be motivated by assessment deadlines, as well as deliberate instructions to refer to the relevant Maths Skills Site modules when completing assessment. The majority of the users of the online support site were those who performed poorly on a diagnostic test administered at the beginning of the course. There was a small but significant effect of Maths Support Site usage with users achieving improved grades for graphing functions compared to non-users. The combination of mathematical backgrounds and prior academic performance also correlated with success in first-year university biochemistry.